An explorative analysis to identify airport business models. (December 2019) - Rotondo, Federico
Abstract: This paper develops a framework based on the strategic management and airport literature, that contextualizes the analysis and measurement of business models in the airport industry. The applicability and usefulness of this framework for interpreting the core logic through which airports create value is then assessed for the Italian airport system, using a cluster analysis on all 45 Italian commercial airports and a total of eight indicators reflecting dimensions of, and questions about, the business model framework. This paper promotes a more structured and comprehensive investigation of the strategic approach of modern airports, viewed as diversified and profit-oriented companies, and paves the way for further empirical analysis aimed at identifying characteristics influencing business model composition and the relationship between business models and airport performance. Highlights: Airports are profit-oriented companies striving to gain a competitive advantage. A framework to interpret and measure airport business models is developed. Airports are grouped on the basis of their value creation processes. Traditional classifications shall be combined with airport business models.